AUDIT DATA ANALYTICS DENGAN MS-EXCEL: USE CASE PEMERIKSAAN PAJAK - Febrian Febrian (Politeknik Keuangan Negara STAN, 2021)
In Tax Auditing, the main activity carried out is the proof of examining the evidence. The Examination of this evidence is done by processing data received from Taxpayers. A growing issue is data from Taxpayers that are processed not only in the form of physical form but also in the form of electronic data such as general ledger. This encourages auditorsto develop Audit Data Analytics (ADA) to be able to perform a series of tests of the electronic data. At the same time, there is a tendency for auditors to use MS-Excel in almost all stages of auditing. Using design science method, this study proposes the artifact findings related to the MS-Excel model and instantiation for the implementation of ADA. The results show the framework for using MS-Excel technology artifacts in the form of steps (1) data preparation and data cleaning (2) application of data analytics (descriptive analytics, diagnostics analytics and predictive analytics). Dalam pemeriksaan pajak , kegiatan utama yang dilaksanakan adalah pengujian bukti. Pengujian bukti ini dilakukan dengan melakukan pengolahan data yang diterima dari Wajib Pajak. Isu yang berkembang adalah data yang diolah dari Wajib Pajak tidak hanya berupa data dalam bentuk fisik, akan tetapi juga berupa data elektronik seperti pembukuan general ledger (buku besar). Hal ini mendorong pemeriksa untuk mengembangkan Audit Data Analytics (ADA) untuk dapat melakukan serangkaian pengujian dari data elektronik tersebut. Pada saat yang sama, terdapat kecenderungan pemeriksa untuk menggunakan MS-Excel dalam hampir semua tahap pemeriksaan. Penelitian ini menggunakan metode design science research mengajukan temuan artefak yang berkaitan dengan model dan instantiasi (instantiation) MS-Excel untuk implementasi ADA. Hasil penelitian didapatkan kerangka penggunaan arterfak teknologi MS-Excel berupa langkah-langkah (1) data preparation dan data cleaning (2) penerapan data analytics (descriptive analytics, diagnostics analytics dan predictive analytics).